Speed-accuracy testing on the Apple iPad(®) provides a quantitative test of upper extremity motor performance in children with dystonia - Bertucco, Matteo (J Child Neurol, 2013)
The only currently available scales for quantitative measurement of the severity of childhood dystonia require human observer ratings and provide poor granularity in the scores for individual limbs. The recent availability of low-cost high-quality touchscreens suggests that these devices could be used for quantification of upper extremity severity. In this study we evaluated the use of an Apple iPad(®) for testing speed and accuracy in a simple pointing task. We compared the abilities or thirteen healthy adults, fifteen healthy children, and sixteen children with primary or secondary dystonia. The linear relation described by Fitts’ Law held for all the groups. The movement time and the information transmitted were age and severity related. Our results provide evidence for the usability and validity of using Fitts’ Law as a quantitative diagnostic tool in children with dystonia. Furthermore, testing on touch-screen tablets may help to guide the design of user interfaces to maximize communication rate for children who depend upon assistive communication devices.